KEEFEKTIFAN PENGEMBANGAN MEDIA DIORAMA BERBASIS AUGMENTED REALITY DALAM PEMBELAJARAN IPAS UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD - Mahmudah, Nur Laila; Novialita Angga Wiratama (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to create a diorama media based on augmented reality as a means to improve the learning outcomes of science in the food chain material for fifth grade students of Tunggul State Elementary School. As well as being used to overcome the minimal use of technology-based media and interactive media in Tunggul State Elementary School. The method used in this study is the development of R&D (Research and Development) which follows the ADDIE development model, this study specifically focuses on the "Implementation", emphasizing the effectiveness test of the media products developed through pre-test and post-test. The results show that the augmented reality-based diorama learning media is very effective, with a score of 83.1% on the post-test results and is declared effective. So the augmented reality-based diorama media is declared feasible and valid for use, and effective in improving learning outcomes.